How nanoscale protein interactions determine the mesoscale dynamic organisation of bacterial outer membrane proteins - Matthieu Chavent (Nature Communications, 2018)
In Escherichia coli, outer membrane protein (OMP) cluster and form islands, but the origin and behaviour of those clusters remains poorly understood. Here authors use coarse grained molecular dynamics simulation and show that their mesoscale simulations recapitulate the restricted diffusion characteristics of OMPs.